2019
DOI: 10.1371/journal.pone.0218456
|View full text |Cite
|
Sign up to set email alerts
|

High similarity of IgG antibody profiles in blood and saliva opens opportunities for saliva based serology

Abstract: Saliva based diagnostics is a rapidly evolving field due to the large diagnostic potential and simple sample collection. Currently only few individual molecules were investigated for their diagnostic capabilities in saliva. A systematic comparison of IgG antibody profiles in saliva and plasma is still missing in scientific literature. Our hypothesis is that IgG profiles in plasma and saliva are highly similar for each individual. As a consequence, one could implement practically any plasma based IgG assay (cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…Although serum is the typical sample type for detecting developed antibodies against many infectious diseases, dried blood spots 7,8 and saliva samples [9][10][11] have also been used successfully. Saliva samples are particularly attractive given the ease and non-invasiveness of sampling, allowing for potential self-collection and substantial scaling of testing.…”
mentioning
confidence: 99%
“…Although serum is the typical sample type for detecting developed antibodies against many infectious diseases, dried blood spots 7,8 and saliva samples [9][10][11] have also been used successfully. Saliva samples are particularly attractive given the ease and non-invasiveness of sampling, allowing for potential self-collection and substantial scaling of testing.…”
mentioning
confidence: 99%
“…Hettegger et al demonstrated that IgG profiles in plasma and saliva are highly similar for each individual and found the anti-HBV IgG antibody from saliva ( Hettegger et al, 2019 ). We therefore tested saliva and serum from a COVID-19 patient.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary IgG concentrations were quantitatively determined by the ELISA method using the ELISA Kit E0544h for research use only (RUO) (EIAab, Wuhan, China). The standard curve ranged from 0 to 5000 pg/mL, the intra-assay variability coefficient was <4.4%, and the inter-assay variability was <7.8%, respectively (r 2 = 0.999, p < 0.001) [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%